JURNAL PENGARUH USER EXPERIENCE (UX) DESIGN TERHADAP KEMUDAHAN PENGGUNA DALAM MENGGUNAKAN APLIKASI CARSWORLD - Joaldrik Ferad Wawolumaja (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2021)
Rapid advances in digital technology are followed by intense competition for digital products. Digital product competition requires every business business to keep trying to facilitate their users as an effort to improve the User Experience of each user. User Experience (UX) Design is an important thing for digital businesses to pay attention to. The ease of user interaction or use of digital products will make the digital product widely used and anti to be abandoned. The better User Experience (UX) Design of a digital product, will make the user more comfortable in using it and as an impact, the user will become a loyal user and may be happy to recommend the product to others. Carsworld app, is the nearest car service online booking application. This application was created in 2018 and has been downloaded more than 10 thousand times on Playstore. This research will discuss about how User Experience (UX) Design affects the ease of users in using Carsworld application. The research was conducted by descriptive quantitative method based on 3 (Three) factors that need to be considered by user experience designer (UX) design as an effort to provide convenience for users of Carsworld application namely Usability, Look and Feel. The results of the study showed that User Experience (UX) Design affects the ease of users in using Carsworld application.